Gravity - Chin, Jason (New York Roaring Brook Press, 2014)
"What keeps objects from floating out of your hand? What if your feet drifted away from the ground? What stops everything from floating into space? Gravity ... Jason Chin has taken a complex subject and made it brilliantly accessible to young readers in this unusual, innovative, and very beautiful book.
Keywords: Gravity -- Juvenile literature; Gravity